Effect of N-acetylcysteine on prevention of contrast-associated acute kidney injury in patients with STEMI undergoing primary percutaneous coronary intervention: a systematic review and meta-analysis of randomised controlled trials. Issue 10 (16th October 2020) - Guo, Zhaodong; Liu, Jin; Lei, Li; Xue, Yan; Liu, Liwei; Huang, Hao; Chen, Shiqun; Liu, Yong; Lin, Yingzhong; Tao, Jianhong; Xu, Qingbo; Wu, Keng; et al.
Abstract : Objective: Several studies evaluating the preventive effect of N-acetylcysteine (NAC) on contrast-associated acute kidney injury (CA-AKI) among patients with ST segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) have suggested inconsistent results and that a systematic review and meta-analysis should be performed. Design: Systematic review and meta-analysis. Data sources: PubMed, MEDLINE, EMBASE, ClinicalTrials.gov and the Cochrane Central databases were searched from inception to 15 November 2019. Eligibility criteria: Randomised controlled trials assessing use of NAC compared with non-use of NAC (eg, placebo) in preventing CA-AKI in patients with STEMI following PPCI were included. Data synthesis: Relative risks with 95% CIs were pooled using a random-effects model. Evidence level of conclusions was assessed by Cochrane GRADE measure. Results: Seven trials including 1710 patients were identified. Compared with non-use of NAC, use of NAC significantly reduced the incidence of CA-AKI by 49% (risk ratio (RR) 0.51, 95% CI 0.31 to 0.82, p<0.01) and all-cause in-hospital mortality by 63% (RR 0.37, 95% CI 0.17 to 0.79, p=0.01). The estimated effects on the requirement for dialysis (RR 0.61, 95% CI 0.11 to 3.38, p=0.24) were not statistically significant. Trial sequential analysis conﬁrmed the true positive of NAC in reducing risk of CA-AKI. Subgroup analyses suggested that the administration of NAC had greater benefits in patients with renal dysfunction and in those receiving oral administration and higher dosage of NAC. Conclusions: NAC intake reduces the risk of CA-AKI and all-cause in-hospital mortality in patients with STEMI undergoing PPCI. The estimated potential benefit of NAC in preventing dialysis was ambiguous, and further high-quality studies are needed. PROSPERO registration number: CRD42020155265.